De l’étable au pressoir : essai d’interprétation des dépendances agricoles gallo-romaines du site des Jacquins ouest à Neulise dans la Loire (42) - Yannick Teyssonneyre (Revue Archéologique du Centre de la France, 2019)
The results of the excavation carried out at the site of Jacquins West in Neulise, in the Loire county, allowed us to fill a persistent archaeological gap in that town. The remains combine to reveal a continuous occupation of the site from the Augustan period to the end of the IIIrd cent.-beginning of the IVth cent. AD. Two rural settlements succeed one another between the Ist and the IIIrd cent., prior to the implementation of a parcel boundary. Changes in the land’s status of the parcel are clearly evidenced three to four times. The first phase corresponds to the settlement and evolution of a large traditional Gallic building, enclosed in palisades and plantation trees. The second phase is materialized by the remains of a large masonry construction, equipped with a craft workshop complex that could be identified as a winery outhouse with a wine press. The last phase corresponds to the implementation of a parcel ditch, supplemented by a second ditch of similar orientation in a second phase. These ditches only border plantation pits observed along the limits of the parcel. The site is then abandoned until the Modern period when a series of vineyard plantations and associated drains are evidenced.